Implementation of an Outcome-Based Education Curriculum in Improving the Competence of Graduates of the Islamic Education Management Study Program - Ach. Baidowi; Syamsudin Syamsudin; Omar Khan (Thawalib: Jurnal Kependidikan Islam, 2026)
Rapid technological development has widened the gap between educational needs and industry needs. Outcome-Based Education aligns curriculum, teaching, and assessment to produce competent, work-ready, and relevant graduates. This research aims to analyze the implementation of Outcome-Based Education in the Islamic Education Management Study Program at Institut Agama Islam Negeri Madura. The study employs a qualitative case study design. Data were collected through interviews, observations, and documentation, and analyzed using data condensation, data display, and conclusion drawing. The findings indicate that the Outcome-Based Education curriculum is systematically designed by integrating graduate learning outcomes, core and supporting courses, achievement standards, and continuous evaluation mechanisms. The curriculum structure and content are aligned with industry requirements, academic development, professional competence, and the cultivation of students’ religious character. The learning process emphasizes active and participatory learning through lectures, discussions, practical training, internships, community service programs, and individual and group assignments to strengthen understanding, skills, independence, and critical thinking. Assessment is conducted through lecturer evaluation, student participation, midterm and final examinations, assignments, scientific article writing, and performance assessment. Continuous curriculum evaluation ensures alignment among learning outcomes, teaching methods, and instructional materials, thereby supporting the development of competent, professional, and competitive graduates.